Intercropping reshapes soil stress resistance and growth promotion capabilities through rhizosphere exudates in conjunction with the microbiome - Wang, Jing; Bai, ChunLi; Tian, Yonglei; Bao, Jian; Liu, JiaoJiao (Frontiers in Microbiology, 2026)
Terrestrial plants can affect the growth and health of neighboring plants through interspecific interactions. Long-term monoculture in agricultural and pastoral production can lead to the occurrence of soil-borne diseases, depletion of nutrients, and a decline in soil microbial diversity, thereby affecting the sustainable development of cultivated ecosystems. In this study, we employed three cultivation patterns: monoculture of Melilotus officinalis (L.) Pall. (M. officinalis), monoculture of Avena sativa L. (A. sativa), and intercropping of M. officinalis and A. sativa. To introduce ecologically protective plants into cultivated ecosystems and investigate the effects of plant root exudates on the recruitment of rhizosphere microbiota of neighboring plants, as well as the disease resistance and growth promotion capabilities of intercropping, we conducted non-targeted metabolomics and metagenomics analyses on root exudates and soil microbiota. The sequencing data obtained provided strong evidence for the interaction mechanisms between root exudates and microorganisms in intercropping ecosystems. We observed that in intercropping ecosystems, the abundance and variety of root exudates were more similar to those of the crop plants. The differential metabolites between intercropping and A. sativa were inclined to be chemically defensive, while those between intercropping and M. officinalis were more inclined to promote material synthesis. Compared with A. sativa, intercropping enhances the alpha and beta diversity of soil microbial communities, particularly increasing the enrichment abundance in pathways such as the bacterial secretion system, sulfur metabolism, and phenylpropanoid biosynthesis, which is closely associated with the suppression of soil-borne pathogens. Compared with M. officinalis, intercropping further enhanced the synthesis of plant-available substances in the soil, driving microorganisms to optimize the levels of carbon, nitrogen, and trace elements in the soil. In comparison, intercropping had a significant impact on the aggregation of soil-specific microorganisms, which can optimize nitrogen utilization to promote plant growth and enhance plant defense and stress tolerance. The results of this study will provide a theoretical basis for cultivated ecosystems and sustainable land management.